Feasibility of 3-Dimensional Media-Based Learning for Electrical Vocational High School Students - Abdul Muin Sibuea; Bima Mustaqim (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2024)
The combination of technology 3 Dimensions (3D) educational content is designed to generate innovative ideas that enhance the efficiency and engagement of teaching and learning in real-world situations. Integrating 3D technology into the learning process can make education more enjoyable, fostering students' interest and motivation to learn. This research developed 3D instructional media for a public street lighting material using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The 3D media developed received overwhelmingly positive feedback from students, with over 90% strongly agreeing that this media significantly enhanced their engagement, interest, and critical thinking. These results prominently validate 3D technology as the future of impactful learning. Moving forward, comparative analyses examining the influences of different 3D media designs and interactions on deep learning will further guide best practices. With thoughtful expansion, this research ushers in a new era of reimagined academic engagement via stimulated minds, captivated eyes, and empowered young innovators. The 3D learning revolution has just begun.